Evidence of autoantibodies against cardiac troponin I and sarcomeric myosin in peripartum cardiomyopathy - Haghikia, Arash; Kaya, Ziya; Schwab, Johannes; Westenfeld, Ralf; Ehlermann, Philipp; Bachelier, Katrin; Öttl, Renate; von Kaisenberg, Constantin S.; Katus, Hugo; Bauersachs, Johann; Hilfiker-Kleiner, Denise (Basic research in cardiology, 2015)
Peripartum cardiomyopathy (PPCM) is a major cause of pregnancy-related maternal heart failure that develops towards the end of pregnancy or in the months following delivery. In small retrospective case series, autoimmune responses in the pathogenesis of PPCM have been proposed upon identification of autoantibodies (AABs) to cardiac antigens. However, their clinical and prognostic relevance still remain unclear. In this study, we evaluated the presence of circulating AABs against cardiac sarcomeric myosin (MHC) and troponin I (TnI) in the sera of PPCM patients and in relation to clinical presentation. In this case-control study, 70 patients diagnosed with PPCM and 50 pregnancy-matched healthy women with normal cardiac function were enrolled. Clinical assessment, echocardiography and blood tests were performed at baseline and at 6 ± 2 months follow-up. The presence of serum AABs against MHC (anti-MHC) and TnI (anti-TnI) was determined with a custom-made enzyme-linked immunosorbent assay (ELISA). The seropositivity for these AABs was correlated with the severity of LV dysfunction and the occurrence of pericardial effusion indicative of perimyocardial inflammation at baseline. Potential impact of these AABs on disease progression was evaluated with regard to functional (left ventricular ejection fraction) and clinical improvement at follow-up. Either anti-MHC or anti-TnI or both AABs were detected in the serum of 46 % of PPCM patients and in 8 % of healthy controls. In PPCM the presence of either one of these AABs was associated with significantly lower baseline LVEF and lower rate of full cardiac recovery at follow-up. Patients who were seropositive for anti-TnI AABs showed more frequently pericardial effusion indicative of a more pronounced immune response of the peri-/myocardium in these patients. Further studies are required to clarify cellular and molecular circuits leading to elevated levels of AABs and their pathophysiological relevance for disease initiation and progression in PPCM.
Gesehen am 15.03.2021